Analisis Kekuatan Tarik Komposit Berbasis Serat Daun Nanas Dengan Variasi Fraksi Volume Dalam Matriks Epoxy-Polyester - Munthe, Basten; Negara, Dewa Ngakan Putra; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika, 2025)
Abstract Composite resulting in better mechanical properties than the original material. The use of natural fibers as composite reinforcement is increasingly in demand because of its environmental friendliness and abundant availability. Pineapple leaf fiber has great potential as a reinforcement because of its high tensile strength and potential as an alternative to synthetic fibers. This research aims to examine the effect of variations in the volume fraction of pineapple leaf fibers (5%, 10% and 15%) on the tensile strength of epoxy-polyester matrix based composites. The method applied includes molding the specimen using the hand lay-up technique, followed by tensile testing according to ASTM D3039 standards. The results show that a fiber volume fraction of 5% with parallel fiber orientation (0°) provides the highest tensile strength. However, increasing the fiber volume fraction actually tends to reduce the tensile strength due to the reduced ability of the matrix to bind the fibers. These findings reveal that volume fraction and fiber orientation greatly influence the mechanical properties of pineapple leaf fiber composites, opening opportunities for the application of environmentally friendly composites in various fields. Keywords: Pineapple leaf fibre, fibre orientation, epoxy-polyester resin, tensile test